Effect of roasting duration on the solubility, structure, and IgE-binding capacity of cashew nut proteins. (March 2021) - Yan, Xiaoli; Wang, Yangling; Chen, Yi; Xie, Jianhua; Yu, Qiang
Abstract: Cashew nuts can induce severe allergic reactions in some allergic individuals. In this work, the solubility, structure and IgE-binding capacity of cashew proteins roasted for different durations were compared. The solubility of cashew nut proteins decreased after roasting. Ana o 3 and Ana o 2 was more thermally stable than Ana o 1. The analysis of the structure of cashew extracts by Fourier transform infrared spectroscopy and environmental scanning electron microscopy demonstrated that roasting reduced the contents of β-sheet and β-turn and led to the unfolding and aggregation of cashew protein. The IgE-binding capacity of cashew protein extracts seemed to decrease with the extension of roasting time. Highlights: The thermal stability of Ana o 3 and Ana o 2 is stronger than Ana o 1. Roasted processing could force the structure of cashew nut protein to unfold and aggregate. IgE-binding capacity of cashew nut protein is reduced gradually with the extension of roasting time. The immunoreactivity of cashew protein is closely related to the changes of their structure.